Design of a Dual-band Wearable Antenna Operating at 2.45 GHz and 5.8 GHz for Medical Communication Applications - Rachman, Fajar Aulia; Rahardjo, Eko Tjipto (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Indonesia's natural demographic which consists of 16,771 islands makes it has many challenges in infrastructure development, especially in the health sector. According to data, Indonesia currently has 10,203 Puskesmas and 2,449 hospitals. In terms of the number of medical personnel, currently in Indonesia there are 124,449 medical personnel. However, of the large number of medical personnel, 61.12% are concentrated in Java and Bali. This inequality causes the need for a technology that makes it easier for medical personnel to provide services to the community. Wireless Body Area Network (WBAN) is one of developed technology that supports telemedical services. In WBAN, wearable antenna is needed as a transmitter to transmit data. In this paper, a compact wearable dual band antenna was designed in ISM frequency band of 2.45 GHz and 5.8 GHz. A combination of rectangular shape radiating structure and cross slot is constructed to achieve dual band frequency. Jeans Textile material with permitivity of 1.7 and thickness of 1 mm is used for fabricating the proposed antenna. The size of antenna is 52.3mm x 58.69mm. The proposed antenna is simulated with and without human body panthom using cst software. The simulations result indicates that antenna resonates at frequency 2.45 GHz and 5.8 GHz with peak gains of 6.92 dBi and 6.5 dBi. SAR values when the proposed antenna simulated at wrist phantom ​​are 0.326W/kg and 1.024W/kg. When simulated at chest phantom, the SAR values ​​are 0.554W/kg and 0.394W/kg. Therefore, The proposed wearable antenna design is well suited for telemedical services.